Prosedur Perpanjangan Buku Pelaut Online di Kantor Kesyahbandaran dan Otoritas Pelabuhan Utama Belawan: Langkah-Langkah, Persyaratan, dan Proses Verifikasi - Matthew Fernando Naibaho; Frisca Mareyta Pongoh; Kris Wanto; Teriyanti Teriyanti (KALAO'S MARITIME JOURNAL, 2024)
This research investigates the online Seaman's Book renewal service process at the Belawan Main Port Authority Office and the Belawan City Office. It identifies the obstacles that arise during the renewal process and explores potential solutions to address these challenges. The study aims to provide an understanding of the existing procedures, pinpoint any hindrances, and recommend ways to enhance the efficiency of the service. The Seaman’s Book is an essential document for seafarers, as it serves as a verification of their employment and travel status. Therefore, it is crucial that the renewal process is seamless and accessible, particularly with the increasing demand for online services. The research utilizes qualitative descriptive methods, which are effective for understanding phenomena within a specific context. This approach helps in uncovering the nuances of the Seaman’s Book renewal process, particularly in the context of online services. By gathering in-depth information from the relevant authorities and seafarers, the study aims to reveal insights into the procedural steps, potential bottlenecks, and the overall experience of service users. The findings will help the offices improve their operations and better meet the needs of seafarers. Through the qualitative descriptive method, the research will also examine the existing facilities and infrastructure available at the Belawan Main Port Authority and Belawan City Offices. A key part of the study will be assessing whether the service spaces are adequate for providing comfortable and efficient services to seafarers. The smooth, quick, and precise processing of Seaman's Book renewals largely depends on the availability of sufficient resources and the resolution of obstacles that may arise .